Oxidative inactivation of NiFeSe hydrogenase1. Issue 75 (28th September 2015) - Ceccaldi, Pierre; Marques, Marta C.; Fourmond, Vincent; Pereira, Inês Cardoso; Léger, Christophe
<x xml:space="preserve">Abstract</x> We propose a resolution to the paradox that spectroscopic studies of NiFeSe hydrogenase have not revealed any major signal attributable to NiIII states formed upon reaction with O2, despite the fact that two inactive states are formed upon either aerobic or anaerobic oxidation.